Dissemination of Farm Information through Kisan Mobile Sandesh - Jogender Singh, Kuldeep Singh, Rahul Singh and Ravinder Singh Poonia, (Indian Journal of Extension Education, 2018)
In the information age, the role of appropriate information package and its dissemination to clientele is of paramount importance. It is not enough to generate information but also to ensure that the required information is delivered to the end users at the earliest and with the least dissemination loss. It can be achieved through effective utilization of various media and channels. Though, India has not remained as an exception to this fact and providing farm information to its farmers through different media and channels. Mobile has brought revolution in information and communication and become the medium of masses in rural areas too because of its unique potential of portability and easy availability. Keeping in view of its potential KVK Kurukshetra started dissemination of farm information through SMSs to the farmers. During 2010-11 forty five technical messages have been flashed on farmers mobile which include 12, 16, 02, 01, 02 and 12 messages on crop production, crop protection, horticulture, animal husbandry, soil conservation and others, respectively. Later, CCSHAU, Hisar in collaboration with Indian Meteorological Department has also started weather based agro-advisories to the farmers of Haryana state through SMS in March, 2011. The SMS alert is being sent twice a week. The present study was conducted in two parts i.e. 2010-11 in Kusrukshetra district 2015-16 in Sonipat district of Haryana.